Factor analysis of the heterosexist harassment, rejection, and discrimination scale in lesbian, gay, bisexual, transgender, and queer people of colour. (3rd June 2019) - Smith, Erin R.; Perrin, Paul B.; Sutter, Megan E.
Abstract : The factor structure of the Heterosexist Harassment, Rejection, and Discrimination Scale (HHRDS) was examined in lesbian, gay, bisexual, transgender, and queer (LGBTQ) people of colour. Two hundred participants completed a survey with the HHRDS and several mental health scales. A confirmatory factor analysis suggested the original HHRDS structure fit the data poorly. Exploratory factor analyses found a different 2‐factor structure, consisting of harassment/rejection and family discrimination. Convergent validity analyses demonstrated that family discrimination had the largest association with depression and anxiety, indicating that family discrimination may be particularly salient among LGBTQ people of colour. This study supports the use of the HHRDS in racially/ethnically diverse samples, but with a slightly different factor structure. Examining discriminatory experiences from family members is an important direction for future research in LGBTQ people of colour.